2014
DOI: 10.1371/journal.pgen.1004718
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Role for p48 Homologs in Protecting Dopaminergic Neurons from Oxidative Stress

Abstract: Parkinson's disease (PD) is the most common neurodegenerative movement disorder characterized by the progressive loss of dopaminergic (DA) neurons. Both environmental and genetic factors are thought to contribute to the pathogenesis of PD. Although several genes linked to rare familial PD have been identified, endogenous risk factors for sporadic PD, which account for the majority of PD cases, remain largely unknown. Genome-wide association studies have identified many single nucleotide polymorphisms associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 62 publications
7
65
0
Order By: Relevance
“…During PD pathology, DA neuron death has been suggested to precede and underlie behavioral deficits. In addition to the PPM1/2 cluster, the PAM cluster has been shown to express the Drosophila p48 homolog 48-related-2 (Fer2) to protect DA neurons from oxidative stress and control locomotor activity (Bou Dib et al, 2014). Moreover, cells in the PAM cluster have been mapped to target the horizontal b' lobes of the MB for controlling locomotion (Riemensperger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…During PD pathology, DA neuron death has been suggested to precede and underlie behavioral deficits. In addition to the PPM1/2 cluster, the PAM cluster has been shown to express the Drosophila p48 homolog 48-related-2 (Fer2) to protect DA neurons from oxidative stress and control locomotor activity (Bou Dib et al, 2014). Moreover, cells in the PAM cluster have been mapped to target the horizontal b' lobes of the MB for controlling locomotion (Riemensperger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1), whose individual roles and connectivity are unfolding [16,17]. Startle-induced climbing assay and its variations (such as startle-induced negative geotaxis; SING) are the most commonly used methods to quantify fly's locomotor behavior in comparing organismal phenotypes of flies and human movement disorders [18][19][20][21]. These assays are distinct from recording the natural tendency to climb, known as negative geotaxis, but monitor the rate of climbing response of flies when knocked down to the bottom of a cylinder.…”
Section: Why Use Drosophila For Parkinson's Disease Research?mentioning
confidence: 99%
“…The climbing response is normally rapid, and failure to recover from the "shock" of being knocked-down suggest some defects in the functioning of nervous system in controlling initiation. Noteworthy, recent studies have demonstrated that at least a subset of DA neurons in the protocerebral anterior medial (PAM) cluster has important roles in the climbing response, much like DA neurons in mammalian SNpc, making flies ever relevant model system for the study of PD [18,22,23]. Figure 1.…”
Section: Why Use Drosophila For Parkinson's Disease Research?mentioning
confidence: 99%
See 2 more Smart Citations